Longevity and oviposition of Mediterranean fruit fly (Ceratitis capitata) (Diptera : Tephritidae) fed on a predominantly sugar and a predominantly protein diet - Van der Merwe, Cornelia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2001.